Patterns and Outcomes of Fingertip Reconstruction: A Review of 120 Cases - Humayra, Zaman Ummay; Sharmin, Afrina; Zaman, Taslima; Islam, Tarikul; Khatun, Momena (Journal of the Medical College for Women & Hospital, 2026)
Background: Fingertip injuries are frequent hand trauma encounters and can impair sensibility, fine pinch, and nail stability. In Bangladesh, electrical burns and machine-related injuries are prominent causes. Successful reconstruction aims to preserve length, provide durable sensate coverage, and restore contour with minimal morbidity. Materials and Method: This retrospective review included 120 patients (≥12 years) treated between January 2017 and December 2023 across three private hospitals in Dhaka. Injury level was determined using the Allen classification. Minor tissue loss (Allen I–II) was treated conservatively, while exposed bone or larger volar defects required flap coverage. Reconstructive techniques included cross-finger flap, reverse cross-finger flap, first dorsal metacarpal artery (FDMA) flap, thenar flap, V-Y advancement flap, adipofascial flap, and distant options. Functional outcomes, two-point discrimination, return-to-use time, and early complications were assessed over 4–12 weeks.Results:Electrical burn was the leading mechanism of injury. Allen type IV was most common. Defect size ranged 1–5 cm². Conservative care produced minimal range-of-motion loss. Mean two-point discrimination was 5.7 mm. Early complications occurred in 28.3%, predominantly minor infection and partial flap necrosis, all managed without major re-operation. Most patients regained acceptable contour and sensibility.Conclusion:A stepwise reconstructive algorithm emphasizing the simplest suitable option yields predictable outcomes. Sensate flaps are valuable for thumb and index injuries. In resource-limited environments, thoughtful flap selection allows preservation of length and function with low complication rates. J Med Coll Women Hosp.2026; 22(1): 89-97